A Clinical Study on the Management of Hyperkalemia in a Secondary Care Hospital, Palakkad, Kerala - Aiswarya. A.T (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background To study the management of hyperkalemia association between potassium monitoring and serious hyperkalemia associated adverse outcomes among the patients with diabetes mellitus, CKD, IHD, hypothyroidism and anemia. Materials and methods The study was designed as a hospital based prospective study. A total of 264 patient case data entry form were collected from the medical records department and they are included in the study. Results The hyperkalemic events, 32.95% more occurred in patients were in age group of 61 to 70 years. The rate of hyperkalemia was higher in patients with diabetes mellitus among individual treated with 33.33% of insulin. Patients who experienced hyperkalemia were more likely to be male and 85.95% patients’ showed severity at mild level. 81.43% therapies recommended elimination of potassium from the body by the use of diuretics. Conclusion Hyperkalemia is a significant problem among the patients with diabetes mellitus, hypertension, CKD, IHD and hypothyroid. Various therapeutic options exit for the immediate treatment of the condition including insulin, diuretics, calcium carbonate, calcium gluconate, sodium bicarbonate, salbutamol and calcium polystyrene sulfonate. Prevention currently rests largely upon compliance with diet and a thoughtful use of medication regimen.